Mutation identification of Fabry disease in families with other lysosomal storage disorders. (28th December 2012) - Zampetti, A; Fania, L; Antuzzi, D; Giurdanella, F; Gnarra, M; Bertola, F; Lualdi, S; Filocamo, M; Morrone, A; Feliciani, C
Abstract : Fabry disease (FD) is an X‐linked lysosomal storage disorder (LSD) caused by the deficiency of the enzyme α‐galactosidase. It exhibits a wide clinical spectrum that may lead to a delayed or even missed diagnosis and the real incidence can be underestimated. We report the cases of two unrelated Italian families in whom FD was incidentally diagnosed in two females. In both families, the risk for other lysosomal disorders was known from other members affected by fucosidosis or mucopolysaccharidosis I Hurler/Scheie. Some subjects were simultaneously heterozygous for Fabry and the other lysosomal deficiency. Our study shows that the risk for more than one LSDs can occur in a family pedigree. The diagnosis of Fabry in female probands represents a diagnostic challenge, as symptoms and signs can be variably present because of the random X‐chromosome inactivation.